Molecular Imaging: Computer Reconstruction and Practice - Lemoigne, Yves (Springer, 2017)
This book reports the majority of lectures given during the NATO Advanced Study Institute ASI-982440, which was held at the European Scienti?c Institute of Archamps (ESI, Archamps – France) from November 9 to November 21, 2006. The ASI course was structured in two parts, the ?rst was dedicated to individual imaging techniques while the second is the object of this volume and focused on data modelling and processing and on image archiving and distribution. Courses devoted to nuclear medicine and digital imaging techniques are collected in a c- plementary volume of NATO Science Series entitled “Physics for Medical Imaging Applications” (ISBN 978-1-4020-5650-5). Every year in autumn ESI organises the European School of Medical Physics, which covers a large spectrum of topics ranging from Medical Imaging to Rad- therapy, over a period of ?ve weeks. Thanks to the Cooperative Science and Te- nology sub-programme of the NATO Science Division, weeks two and three were replaced this year by the ASI course dedicated to “Molecular Imaging from Physical Principles to Computer Reconstruction and Practice”. This allowed the participation ofexpertsandstudentsfrom20differentcountries,withdiverseculturalbackground and professional experience (Africa, America, Asia, and Europe). A further positive outcome of NATO ASI participation is the publication of this book, which contains the lectures series contributed by speakers during the second week of the ASI.